1997
DOI: 10.1136/jcp.50.4.294
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal sepsis: an immunocytochemical study of the small intestine mucosa.

Abstract: Studies on this immunological component in critically ill patients are limited by ethical and therapeutic constraints; however, suitable tissues may be obtained from patients whose condition necessitates surgical removal of part of the small bowel. A series of such specimens was retrieved for the present study. Tissues from near the excision margins considered viable by the surgeons and judged to be relatively remote from the primary intraabdominal damage by the pathologists-were selected for immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 21 publications
0
15
0
4
Order By: Relevance
“…Consequently, low levels of this immunoglobulin could preclude bacterial clearance. Coutinho et al [15] reported noticeable reductions in numbers of IgA and IgM plasma cells in intestinal tissues from patients with intra-abdominal sepsis. The association between immunoglobulins levels with survival was not dependent on hemodilution, as supported in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, low levels of this immunoglobulin could preclude bacterial clearance. Coutinho et al [15] reported noticeable reductions in numbers of IgA and IgM plasma cells in intestinal tissues from patients with intra-abdominal sepsis. The association between immunoglobulins levels with survival was not dependent on hemodilution, as supported in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Lightfoot et al (71) have recently shown that major burn trauma to rats is associated with an almost 100-fold increase in cardiac myocyte apoptosis. Human studies of septic shock have suggested increased apoptosis primarily in cells of the immune system, although the phenomenon has also been noted in intestinal epithelial cells (73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…One report showed that restraint stress does not reduce the number of IgA-producing cells in intestinal lamina propria of mice [12]. The other studies comparing the number of IgA + cells in intestinal and respiratory mucosa used stress protocols related to exercise or sickness, and are therefore difficult to compare to the current contribution [64,65].…”
Section: Discussionmentioning
confidence: 93%